THE EFFECT OF DRUGS ON HUMAN PHYSIOLOGY AND MEASURES TO FIGHT AGAINST DRUGS (E Conference Zone, 2022)
The growing number of drug addicts in the world and in the country is currently affecting many young and middle-aged people. Of course, this is due to the fact that most people are overly entertained. And it will cost them their lives and their health. This article discusses the effects of drugs on human physiology and measures to combat them.